Angels Fall - Nora Roberts (New York Jove Books, 2007)
Reece Gilmore has come a long way to see the stunning view below her. As the sole survivor of a brutal crime back East, she has been on the run, desperately fighting the nightmares and panic attacks that haunt her. Reece settles in Angel's Fist, Wyoming--temporarily, at least--and takes a job at a local diner. And now she's hiked this mountain all by herself. It was glorious, she thought, as she peered through her binoculars at the Snake River churning below. Then Reece saw the man and woman on the opposite bank. Arguing. Fighting. And suddenly, the man was on top of the woman, his hands around her throat ... --From publisher description
Keywords: Literature (3GdCOHs; General -- Fiction; Murder; Victims of crimes -- Fiction